An event of simultaneous activity of atmospheric gravity waves and meteotsunami in the inner continental shelf of the Buenos Aires Province, Argentina. (1st February 2020) - Perez, Iael; Dragani, Walter; Saucedo, Marcos; Godoy, Alejandro; Cerne, Bibiana
Abstract: The aim of this paper is to investigate an event of simultaneous activity of atmospheric gravity waves (AGW) and meteotsunami recorded on December 1–2, 2013, in the inner continental shelf of Buenos Aires Province, Argentina. The Weather Research and Forecasting (WRF) model was implemented to simulate high-frequency atmospheric disturbances. WRF outputs were used to drive an oceanic model (Tide And Wind Induced Circulation, TAWIC) to reproduce the observed meteotsunami. WRF model was validated using twenty-five data series of atmospheric pressure, and a high-resolution atmospheric pressure data series observed at Mar del Plata. TAWIC model was validated using a high-resolution sea-level data series recorded at Mar del Plata. WRF model was able to capture the main synoptic and mesoscale features during the simulated period. Wavelet and cross-wavelet analysis showed that the spectral structures of the AGW and meteotsunami were satisfactorily simulated. AGW propagated following the storm track, and its activity area was mainly bounded between Mar del Plata and Punta Médanos. Numerical simulations showed that the meteotsunami was practically negligible westwards Quequén Port and at the Río de la Plata mouth, and that it was amplified when the AGW propagated along the coast. Numerical results suggest that the meteotsunami can be seen like an ocean edge wave propagating along the coast of the Buenos Aires Province. Highlights: An event of atmospheric gravity waves (AGW) and meteotsunami is investigated. The study region is the continental shelf of Buenos Aires Province, Argentina. AGW were simulated with WRF model, and used as forcing of an ocean model. WRF model simulated the main synoptic and mesoscale features in the region. The meteotsunami was satisfactorily simulated by the ocean model.